2019
DOI: 10.5965/223811711812019081
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da fertilidade de gemas de variedades de uvas viníferas cultivadas em região de elevada altitude de Santa Catarina

Abstract: Observa-se na região de elevada altitude de Santa Catarina baixo índice de fertilidade de gemas de variedades de uvas viníferas, sendo as variações na produtividade umas das maiores fontes de dúvidas na produção vitivinícola. Nesse contexto, tem-se como objetivo deste trabalho, avaliar a fertilidade de gemas de variedades viníferas em região de elevada altitude de Santa Catarina. O presente estudo foi realizado na safra 2016/2017. Os ramos e as gemas foram retiradas de um vinhedo comercial, localizado no munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(8 reference statements)
0
4
0
3
Order By: Relevance
“…Studies with the French varieties Cabernet Sauvignon, Chardonnay, Merlot, Sauvignon Blanc, Cabernet Franc, and the Italian genotypes Nebbiolo, Greco di Tufo and Coda di Volpe grown in Santa Catarina State also observed low fertility of basal buds of the studied varieties (Rosa et al 2014, Munhoz et al 2016, Würz et al 2019). Cultivar has a major effect on dormant bud fruitfulness with genotypes differences observed for the number fertilre shoots, number of clusters per shoot, and bud position of the cluster on the shoot.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Studies with the French varieties Cabernet Sauvignon, Chardonnay, Merlot, Sauvignon Blanc, Cabernet Franc, and the Italian genotypes Nebbiolo, Greco di Tufo and Coda di Volpe grown in Santa Catarina State also observed low fertility of basal buds of the studied varieties (Rosa et al 2014, Munhoz et al 2016, Würz et al 2019). Cultivar has a major effect on dormant bud fruitfulness with genotypes differences observed for the number fertilre shoots, number of clusters per shoot, and bud position of the cluster on the shoot.…”
Section: Resultsmentioning
confidence: 88%
“…And long pruning would be more appropriate for Fiano, Garganega, Rebo and Teroldego (Calò et al 2006). While in altitude conditions of Santa Catarina State it was observed that long pruning would be more suitable for Rebo and Nebbiolo, due to the low bud fertility in the basal position of the cane Würz et al 2018).…”
Section: Varietymentioning
confidence: 99%
See 2 more Smart Citations
“…As variações na produtividade são umas das maiores fontes de dúvidas na produção vitivinícola (Wurz et al, 2019a), sendo o aumento da carga de gemas planta -1 , uma das alternativas para aumentar a produtividade dos vinhedos e melhorar o seu equilíbrio vegetativo seria através da poda de inverno (Wurz et al, 2020).…”
Section: Introductionunclassified